Сейсмічний прогноз і класифікація Верхньосерпуховських біогермних споруд північних окраїн Донбасу - Хабанець, І.А.; Тяпкіна, О.М. (Геоінформатика, 2015)
Статтю присвячено актуальній на сьогодні проблемі вивчення і картування біогермних споруд як нафтогазо-перспективних об’єктів. Узагальнено практичний досвід, накопичений дослідниками цієї проблеми в межах північних окраїн Донбасу. З використанням нових сейсмічних даних, отриманих в 2009—2012 рр., розроблено методику виділення і класифікації біогермних споруд, яка ґрунтується на сейсмофаціальному і морфогенетичному аналізах. В основу сейсмофаціального аналізу покладено вивчення сейсмічних зображень, що дало змогу виділити кілька пошукових ознак. Класифікацію біогермних споруд проведено з використанням морфогенетичного аналізу. В результаті встановленого взаємозв’язку між морфологією біогермних споруд і тектонічною основою, на якій вони формувалися, виділено два типи біогермів — тектоногенний і седиментогенний. Наведено практичні результати застосування запропонованої методики, за допомогою якої виділено біогермні споруди та структуровано їх за умовами утворення і розміщення на площі досліджень. Статья посвящена актуальной проблеме изучения и картирования биогермных построек как нефтегазоперспективных объектов. Обобщен практический опыт, накопленный исследователями этой проблемы в пределах северных окраин Донбасса. С привлечением новых сейсмических данных, полученных в 2009—2012гг., разработана методика выделения и классификации биогермных построек, базирующаяся на сейсмофациальном и морфогенетическом анализах. В основу сейсмофациального анализа положено изучение сейсмических изображений, что позволило выделить поисковые признаки. Классификация биогермных построек проведена с использованием морфогенетического анализа. В результате установленной связи между морфологией биогермных построек и тектонической основой, на которой они формировались, выделено два типа биогермных построек — тектоногенный и седиментогенный. Представлены практические результаты применения указанной методики, позволившей выделить биогермные постройки, структурировать их по условиям образования и размещению на площади исследований. Purpose. Carbonate buildup structures are favorable reservoir for gas and oil accumulation. Large part of world's oil and gas fields were explored in carbonate structures represented by different morphological forms, influenced by the intensification of basin burial in a particular geosyncline or platform geotectonic province. At present, the lack low of deep drilling and seismic data in the northern part of Donets Basin does not allow us to definitively delineate and estimate resources of carbonate buildups formed in favorable conditions for carbonate depositions during Serpukhovian time, even taking into account large amount of publications related to this area. These are the reasons why nowadays problems related to exploration and appraisal of new buildup structures based on information from processing and interpretation of recently acquired 3D seismic data remain of current importance.
Design/methodology/approach. The proposed methodology of buildup structure delineation is based on determination of patterns and exploration features based on seismic facies and morphogenetic analysis.
Findings. A methodology of delineation and classification of carbonate buildups is suggested. This methodology permits to determine the morphology, depositional characteristics and patterns of areal distribution of carbonate buildup structures in this region.
Practical value/implications. A methodology of delineation and classification of carbonate buildup structures has been developed and successfully applied in a 250 square kilometer area from the northern Donets Basin. The results of the research will promote successful exploration of buildup structures in this and other areas of the northern Donets Basin.